2012
DOI: 10.1039/c2cc30779k
|View full text |Cite
|
Sign up to set email alerts
|

Evolving P450pyr hydroxylase for highly enantioselective hydroxylation at non-activated carbon atom

Abstract: Directed evolution of a monooxygenase to achieve very high enantioselectivity for hydroxylation at non-activated carbon atoms is demonstrated for the first time, where a triple mutant of P450pyr hydroxylase is obtained via determination of enzyme structure, iterative saturation mutagenesis, and high-throughput screening with a MS-based ee assay to increase the product ee from 53% to 98% for the hydroxylation of N-benzyl pyrrolidine to (S)-N-benzyl 3-hydroxypyrrolidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…The top six unique hits were identified and are shown in Table 3. The results showed that CYP153D17 had the highest degree of structural similarity with P450pyr (PDB code, 3RWL) [13] and that CYP153D17 shared structural similarity with CYP124 (PDB code, 2WM4) [25], CYP142 (PDB code, 2XKR) [26], P450terp (PDB code, 1CPT) [27], CYP125 (PDB code, 2X5W) [28], and CYP108D1 (PDB code, 3TKT) [29]. Sequence alignments of these proteins revealed that several residues constituting the hydrophobic substrate-binding pocket of CYP153D17 were highly conserved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top six unique hits were identified and are shown in Table 3. The results showed that CYP153D17 had the highest degree of structural similarity with P450pyr (PDB code, 3RWL) [13] and that CYP153D17 shared structural similarity with CYP124 (PDB code, 2WM4) [25], CYP142 (PDB code, 2XKR) [26], P450terp (PDB code, 1CPT) [27], CYP125 (PDB code, 2X5W) [28], and CYP108D1 (PDB code, 3TKT) [29]. Sequence alignments of these proteins revealed that several residues constituting the hydrophobic substrate-binding pocket of CYP153D17 were highly conserved.…”
Section: Resultsmentioning
confidence: 99%
“…Several bacterial CYPs in the CYP153 family have been characterized [11,12]. In 2012, the crystal structure of CYP153A7 (P450pyr) was determined [13]. In addition, researchers have attempted to engineer enzymes from the CYP101 and CYP102 families for alkane hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, P450 CAM from P. putida [132,133] and P450 pyr from Sphingomonas sp. HXN-200 [33,134] have been improved for epoxidation by site-directed mutagenesis (Table 13.1, entries 3-5).…”
Section: Protein Engineering Of Cytochrome P450smentioning
confidence: 99%
“…Although recursive epPCR proved to be successful in this study, it can be anticipated that saturation mutagenesis at active site residues and possibly ISM are likely to be more efficient, probably providing a high diversity of mutants showing different site-selectivity. Indeed, this was demonstrated in a subsequent study in which tryptamine (40) was used as the model substrate (Scheme 14). 58 At the outset of the project, the goal was defined as the search for three different RebH mutants leading to the ortho-, meta-and para-products 41, 42 and 43, respectively.…”
Section: Engineering Site-selectivity Of Halogenasesmentioning
confidence: 99%
“…In a later study, (S)-selectivity were boosted to 98% ee by applying several rounds of structureguided ISM, an impressive achievement. 40 The first reported example of enhancing site-selectivity of a CYP while evolving both (R)-and (S)-selectivity on an optional basis concerns oxidative hydroxylation of compound 14 catalyzed by P450-BM3 (Scheme 9). 41 WT is only 84% regioselective with moderate preference for allylic position C3, while enantioselectivity is poor in slight favor of (R)-15 (34% ee).…”
mentioning
confidence: 99%